Use the elimination method to solve the follow system of equations. 4x−2y=20 4 ��� − 2 ��� = 20 12x−2y=36 12 ��� − 2 ��� = 36 (1 point) Responses (−1,%C2%A0−2) ( − 1 , %C2%A0 − 2 ) (−1,%C2%A0−2) ( − 1 , %C2%A0 − 2 ) (−2,%C2%A06) ( − 2 , %C2%A0 6 ) (−2,%C2%A06) ( − 2 , %C2%A0 6 ) (2,−6) ( 2 , − 6 ) open paren 2 comma negative 6 close paren (4,−2)

1 answer

First, we can simplify the equations by dividing both sides by 2:

1) 2x - y = 10
2) 6x - y = 18

Next, we can multiply equation 1 by -1 and add it to equation 2 to eliminate y:

-1(2x - y) = -1(10)
-2x + y = -10

Adding this to equation 2:

6x - y + (-2x + y) = 18 - 10
4x = 8
x = 2

Now, we can substitute the value of x back into equation 1 to solve for y:

2(2) - y = 10
4 - y = 10
-y = 6
y = -6

Therefore, the solution to the system of equations is x = 2 and y = -6, which is represented as (2,-6).